KEBIASAAN BUANG AIR BESAR SEMBARANGAN (BABS) DI DESA TANJUNG PERANAP, TEBING TINGGI BARAT - Nila Puspita Sari; Susanti . (Jurnal Kesehatan, 2021)
Open Defecation is one of problem in developing country such as Indonesia. Indonesia is still currently also facing problems in the field of sanitation and healthy living behaviour. Tanjung Peranap is one of five villages that have open defecation problems (21,8%). The research objective was to find out the factors related to open defecation in Tanjung Peranap village, the working area of ​​the Alai Public Health Centre in Tebingtinggi Barat District. This research method was observation through a quantitative approach with cross-sectional design. Total samples were 191 respondents by simple random sampling. The analysis used univariate and bivariate with Chi Square-test, the measuring instrument is a questionnaire accompanied by processing data through a computer. The results showed that there was a relationship between knowledge, action, family income, ability of means, role of health staff with open defecation free (p value = 0,001;0,001;0,001; 0,018; 0,001; and 0,001). Conclusions are all related research variables. Suggestions for respondents are the improvement of environmental sanitation facilities in the form of providing family latrines  in the village of Peranap as an effort to prevent transmission of diseases from feces.